2014
DOI: 10.1002/cbic.201402052
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Photophysical Properties and Incorporation of a Highly Emissive and Environment‐Sensitive Uridine Analogue Based on the Lucifer Chromophore

Abstract: The majority of fluorescent nucleoside analogues used in nucleic acid studies have excitation maxima in the UV region and show very low fluorescence within oligonucleotides (ONs); hence, they cannot be utilised with certain fluorescence methods and for cell-based analysis. Here, we describe the synthesis, photophysical properties and incorporation of a highly emissive and environment-sensitive uridine analogue, derived by attaching a Lucifer chromophore (1,8-naphthalimide core) at the 5-position of uracil. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…A similar increase in stability (2.7 °C) was observed for tC- and tC O -incorporation into DNA, and presumably reflects that the increased base stacking interactions act to stabilize the duplex structure 30, 31 . In the few reports on fluorescent base analogues in RNA, a slightly stabilizing effect was also reported for the emissive guanosine isomorph, th G 47 , whereas a negligible effect was reported for the uridine analogue U Dz  48 , and a destabilizing effect was reported for benzo [b] thiophene- 49 , benzofuran- 50 and naphthalimide-conjugated 51 uridine analogues.…”
Section: Resultsmentioning
confidence: 99%
“…A similar increase in stability (2.7 °C) was observed for tC- and tC O -incorporation into DNA, and presumably reflects that the increased base stacking interactions act to stabilize the duplex structure 30, 31 . In the few reports on fluorescent base analogues in RNA, a slightly stabilizing effect was also reported for the emissive guanosine isomorph, th G 47 , whereas a negligible effect was reported for the uridine analogue U Dz  48 , and a destabilizing effect was reported for benzo [b] thiophene- 49 , benzofuran- 50 and naphthalimide-conjugated 51 uridine analogues.…”
Section: Resultsmentioning
confidence: 99%
“…Design and synthesis of ethynyl-extended regioisomersof HBT Various groups with different Hammett substituent constants (s)w ere introducedv ia Sonogashira cross-couplingr eactions between terminal alkynes and aryl halides. [27][28][29] The commercially available regioisomers of brominated salicylaldehyde could make further chemical modification feasible. Synthetic strategies of the 3'-, 4'-a nd 6-substituted regioisomers of HBT are outlinedi nS cheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies and literature reports indicated that responsive fluorescent nucleobase analogues can be generated by attaching heterocyclic moieties onto nucleobases . As part of our continuous efforts to develop responsive fluorescent probes, we identified the naphthalimide core of Lucifer dye as a promising heterocyclic moiety to build the fluorescent PNA building block for the following reasons . The Lucifer dye, based on a 1,8‐naphthalimide core, has an excitation and emission maximum in the visible region with a large Stokes shift and high quantum yield .…”
Section: Resultsmentioning
confidence: 99%